Manifestasi Nilai Kemanusiaan dalam Cerpen Kontemporer dan Relevansinya Sebagai Materi - Eny Junyanti; Nazla Maharani Umaya (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
This research examines the manifestation of humanistic values in six selected short stories from Kompas in 2021-2022 as an alternative literary teaching material. The phenomenon of declining understanding of humanitarian values among students and the importance of instilling these values through literary works serve as the background for this study. The goal is to identify and analyze the representation of humanism in contemporary Indonesian literature. The research method uses a descriptive qualitative approach with content analysis techniques. The analysis results show that the six short stories studied are rich in humanistic values such as openness, responsibility, solidarity, justice, self-sacrifice, care, and mutual assistance. The structure of a short story, including characters and setting, plays an important role in conveying those values. "The Holy Family" depicts openness, "The Three-Colored Bahar Roots" emphasizes sacrifice, "This City is a Well" explores solidarity, "About the Name of Majid Pucuk" showcases the struggle for justice, "The House that Always Smells Bad" illustrates mutual aid, and "The Fading Spark in His Eyes" highlights family care. This finding has implications for the development of more contextual literature teaching materials, encouraging a deeper understanding of humanism among students.